Social Status of Agbè and Kete: A Historical and Functional Yorùbá Oral Literary Perspectives - Kíaríbẹ̀ẹ́ Luqman Abísọ́lá (Universitas Ahmad Dahlan, 2022)
Agbè (a gourd) and kete (a calabash pot) are both utensils in the Yorùbá socio-cultural setting. They are also made musical instruments in orin agbè and orin kete. Because both objects are structurally and functionally interwoven, many people could not delineate their status. As a result, some even take them for one. This has resulted in cultural and literary misplacement of the priority of the objects. Sequel to the identified problem, this study attempts a critical cultural and literary analysis of agbè and kete in order to validate their socio-cultural and literary status. New historicism is used as the theoretical framework. The study adopts an ethnological research design. Yorùbá oral historical and literary materials are the base of the study’s critical analysis. Data were collected among the elders in Ìbàràpá and Òkè-Ògún, and some other parts of the Yorùbáland. It is revealed in the analysis that, agbè and kete’s uses to some extent are complementary. Thus, agbè is more useful than kete. Agbè is considered for keeping precious items, and as a musical instrument, it is having social status. Kete on the hand is also having a social status as it is both used as utensil and musical instrument. However, kete’s religious status is validated for its use in Ọbàtálá religious service. Using agbè to save precious items is not enough to consider it more important than kete as kete in the religious context of Ọbàtálá is also used for a significant religious function.